Characterization of new negative temperature coefficient thermistors based on Zn–Ni–O system - Xiang Sun; Hong Zhang; Ya Liu; Jia Guo; Zhicheng Li (Journal of Advanced Ceramics, 2016)
Abstract Y2O3-doped Zn1-x Ni x O (x = 0, 0.3, 0.4, 0.5, 0.6, 0.7, and 0.9) powders were prepared by a wet chemical synthesis method, and the related ceramics were obtained by the traditional ceramic sintering technology. The phases and related electrical properties of the ceramics were investigated. The analysis of X-ray diffraction (XRD) indicates that the prepared ceramics with Ni substitution have a cubic crystalline structure. The resistance–temperature feature indicates that all the ceramics show a typical effect of negative temperature coefficient (NTC) of resistivity with the thermal constants between 3998 and 5464 K, and have high cyclical stability in a temperature range from 25 to 300 °C. The impedance analysis reveals that both grain effect and grain boundary effect contribute collectively to the NTC effect. The electron hopping and band conduction models are proposed for the grain (bulk) conduction, and the thermally activated charge carrier transport overcoming the energy barrier is suggested for the grain boundary conduction.